A Kv2 inhibitor combination reveals native neuronal conductances consistent with Kv2/KvS heteromers - Robert G Stewart; Matthew James Marquis; Sooyeon Jo; Brandon J Harris; Aman S Aberra; Verity Cook; Zachary Whiddon; Vladimir Yarov-Yarovoy; Michael Ferns; Jon T Sack (eLife)
KvS proteins are voltage-gated potassium channel subunits that form functional channels when assembled into heteromers with Kv2.1 (KCNB1) or Kv2.2 (KCNB2). Mammals have 10 KvS subunits: Kv5.1 (KCNF1), Kv6.1 (KCNG1), Kv6.2 (KCNG2), Kv6.3 (KCNG3), Kv6.4 (KCNG4), Kv8.1 (KCNV1), Kv8.2 (KCNV2), Kv9.1 (KCNS1), Kv9.2 (KCNS2), and Kv9.3 (KCNS3). Electrically excitable cells broadly express channels containing Kv2 subunits and most neurons have substantial Kv2 conductance. However, whether KvS subunits contribute to these conductances has not been clear, leaving the physiological roles of KvS subunits poorly understood. Here, we identify that two potent Kv2 inhibitors, used in combination, can distinguish conductances of Kv2/KvS heteromers and Kv2-only channels. We find that Kv5, Kv6, Kv8, or Kv9-containing channels are resistant to the Kv2-selective pore-blocker RY785 yet remain sensitive to the Kv2-selective voltage sensor modulator guangxitoxin-1E (GxTX). Using these inhibitors in mouse superior cervical ganglion neurons, we find predominantly RY785-sensitive conductances consistent with channels composed entirely of Kv2 subunits. In contrast, RY785-resistant but GxTX-sensitive conductances consistent with Kv2/KvS heteromeric channels predominate in mouse and human dorsal root ganglion neurons. These results establish an approach to pharmacologically distinguish conductances of Kv2/KvS heteromers from Kv2-only channels, enabling investigation of the physiological roles of endogenous KvS subunits. These findings suggest that drugs which distinguish KvS subunits could modulate electrical activity of subsets of Kv2-expressing cell types.